CORRELATION BETWEEN DENTAL FLUOROSIS AND GROUNDWATER CONSUMPTION IN CHILDREN AGED 8-15 YEARS IN THE KARST AREA BANYUMAS - Hidayat, Egi Gibbons; Satrio, Rinawati; Hidayah, Riski Amalia; Widodo, Haris Budi; Oktadewi, Fitri Diah (Mandala Of Health, 2025)
Background: dental fluorosis is a condition of tooth growth and development that causes spots and brittle teeth. The cause of dental fluorosis is chronic fluoride intoxication due to consumption of fluoridated water during the tooth development period. One type of water with a high fluoride content is groundwater in karst areas. Groundwater in Darmakradenan village containing 1,9 mg/L fluoride. The vast majority of the locals consume groundwater as drinking water. Aim: to determine the association between groundwater consumption and the incidence of dental fluorosis. Methods: an analytic-observational with a cross-sectional approach. The research population consisted of residents aged 8–15 years in Darmakradenan Village, Ajibarang District, and Banyumas Regency. Purposive sampling was implemented for selecting research participants, with a total of 90 participants who divided into two groups: consumed groundwater and refilled drinking water. The Dean's Index is used to examine the status of dental fluorosis. Analysis data used Chi-square test. Result: there was an association between groundwater consumption and dental fluorosis (p < 0,05, CC = 0,277). Conclusion: there is an association between groundwater consumption in karst areas and the incidence of dental fluorosis.